Health evaluation of captive Malayan sun bear (Helarctos malayanus Horsfield) in zoos in Peninsular Malaysia - Che' Amat, Azlan (2011)
The health status of 19 captive Malayan Sun Bears, 4 males and 15 females, weighing between 31 – 87 kilograms were used in this study. The objectives of the study include the analysis of blood to obtain baseline blood parameters, blood analysis of some viral, bacteria and faecal analysis of parasitic organisms, and comparison of 2 anaesthetic drugs. Animals in Zoo Negara were immobilized with Zoletil®-Xylazine (ZX) and Zoletil®-Ketamine-Xylazine (ZKX) combination was used in Taiping Zoo & Night Safari. Blood and fresh faecal samples were used for study analysis.All Sun Bears were sampled to determine their exposure some important pathogens. There was no evidence of exposure to Canine Adenovirus (CAV), Canine Distemper Virus (CDV) by using Serum Neutralization Test (SNT). Seroprevalence of two Brucella sp. and 14 Leptospira serovars were also not detected by using Rose Bengal Plate Test (RBPT) and Microscopic Agglutination Test (MAT) respectively. Simple faecal floatation technique detected strongyles (hookworm) ova only in two animals but in very low numbers. No blood parasites were found. Haematology studies includes PCV, RBC count, differential counts for leucocytes, haemoglobin, plasma protein, PT and APTT. A total of 26 biochemistry parameters were analyzed namely Na, K, Cl¯, inorganic phosphate, BUN, creatinine, glucose, cholesterol, total bilirubin, total protein, ALT, ALP, AST, CK, globulin, albumin, globulin-albumin ratio, amylase, LDH, lipase, lactate, uric acid, triglyceride and GGT. Male and female comparison showed only haemaglobin had significant higher value in males. Leucocytes and segmented neutrophil were significantly high in subadult. Current value showed low haemaglobin and leucocytes compared to previous data. Preliminary data on anticoagulation factor namely PT and APTT were recorded. Biochemistry showed ALT, GGT and CK were significantly higher in males. Subadult group showed higher value of ALT, GGT, CK, LDH and albumin. Our current data showed lower value of calcium, inorganic phosphate, BUN and AST compared to previous data. Additional preliminary data on GGT, amylase, CK, total triglyceride, lipase and lactate were recorded. The effects of 2 anaesthetic drugs, ZX and ZKX combinations were documented in this species. Both drugs effectively immobilized the sun bears but induction with ZKX produced more rapid, smooth induction and good analgesia. Physiological parameters such as respiratory rate, pulse rate, SpO2, MAP and rectal temperature were within a good range for both treatment group. The used of yohimbine to reversed the ZKX give a better recovery two times faster than without using yohimbine in ZX group. Thus, results obtained in the present study suggested that all captive Malayan Sun Bears in the zoo were healthy as shown by their blood haematology and serum biochemistry, were within the data previously documented in the same species. No seroprevalence were detected for CAV, CDV, Leptospira sp. and Brucella sp. in all bears and this indicates these animals are not protected against these pathogens. Parasites found by faecal examination was not significant but preventive measures should be periodically done. The ZKX may be a better choice of immobilizing the sun bear due to rapid, smooth induction, good analgesia and rapid recovery by using yohimbine.